Pengaruh Risiko Likuiditas dan Risiko Kredit terhadap Kinerja Keuangan pada Bank Digital Periode 2020-2024 - Indri Iswardhani; Muhammad Rijal Alim Rahmat; Nur Fadilah Ayu Sandira; Nulthazam Sarah; Sri Astuti Nasir (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of liquidity risk and credit risk on the financial performance of digital banks listed on the Indonesia Stock Exchange for the 2020-2024 period. The research employs an explanatory quantitative approach with a sample of four digital banks selected through purposive sampling. Data were analyzed using multiple linear regression with independent variables Loan to Deposit Ratio (LDR) for liquidity risk and Non-Performing Loan (NPL) for credit risk, and the dependent variable Return on Assets (ROA) for financial performance.The results show that simultaneously, LDR and NPL have a significant effect on ROA. Partially, LDR proves to have a positive and significant effect on ROA, while NPL does not show a significant effect. These findings indicate that liquidity management plays a more critical role in determining the financial performance of digital banks compared to credit risk. This study recommends that digital bank management focus on optimizing liquidity management to improve profitability, while still paying attention to the potential impact of credit risk in the long term.